2007
DOI: 10.1210/jc.2006-1815
|View full text |Cite
|
Sign up to set email alerts
|

Retinol-Binding Protein 4 Is Associated with Insulin Resistance and Body Fat Distribution in Nonobese Subjects without Type 2 Diabetes

Abstract: These findings indicate a relationship between RBP4, insulin sensitivity, and percent trunk fat in individuals who may not have features of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
3
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 23 publications
11
120
3
8
Order By: Relevance
“…Stefan et al (22) convincingly demonstrated that circulating RBP-4 positively correlates with HOMA-IR in healthy subjects. A positive association between RBP-4 levels and insulin resistance is also shown in obese and nonobese adolescents (18); in subjects with obesity, IGT, or type 2 diabetes; in nonobese, nondiabetic subjects with a strong family history of type 2 diabetes (5); and in nonobese individuals without a family history or diagnosis of diabetes (23). In contrast, no correlation between RBP-4 and insulin resistance is found in Aboriginal Canadian women and white women (24).…”
Section: Univariate and Multivariate Correlationsmentioning
confidence: 94%
“…Stefan et al (22) convincingly demonstrated that circulating RBP-4 positively correlates with HOMA-IR in healthy subjects. A positive association between RBP-4 levels and insulin resistance is also shown in obese and nonobese adolescents (18); in subjects with obesity, IGT, or type 2 diabetes; in nonobese, nondiabetic subjects with a strong family history of type 2 diabetes (5); and in nonobese individuals without a family history or diagnosis of diabetes (23). In contrast, no correlation between RBP-4 and insulin resistance is found in Aboriginal Canadian women and white women (24).…”
Section: Univariate and Multivariate Correlationsmentioning
confidence: 94%
“…For instance, plasma levels of retinol-binding protein 4, a protein released from adipocytes and associated with insulin resistance, 121 correlate with trunk fat mass. 122,123 Further, serum vaspin, an insulin-sensitizing adipokine, shows an interesting sexual dimorphism with levels higher in women. 124 For these, and for other emerging adipokines, little is known regarding the specific role of regional adipose tissue in their production, secretion and function in human metabolism.…”
Section: Other Adipokinesmentioning
confidence: 99%
“…RBP4 is highly expressed in liver as well as adipose tissue, and its circulating levels have been shown to correlate with obesity and insulin resistance in rodents (Yang et al 2005). In humans, RBP4 levels have been shown to be elevated in several groups of insulin-resistant subjects (Graham et al 2006;Gavi et al 2007), but not all studies have shown such differences (Janke et al 2006;Takashima et al 2006). It has been suggested that increased serum RBP4 levels might contribute to insulin resistance by impairing insulin-stimulated glucose uptake in muscles and elevating hepatic glucose production, although the mechanism is not fully clear (Yang et al 2005).…”
Section: Adipokinesmentioning
confidence: 99%